The impact of scent on visual attention - Chong, Trinetta Chiao Sing (2013)
This research is to determine whether a scent has an effect on one's visual attention towards a congruent visual cue or textual cue in the context of an advertisement, to determine whether a scent has an effect on one's visual attention towards an object of a semantically congruent color in the context of an advertisement, to determine whether a scent has an effect on one's visual attention towards a semantically congruent visual or textual cue in the context of an advertisement. [1st Award]